Cooking Class Dengan Pendekatan Steam Guna Melatih Motorik Halus Siswa di Sekolah Penggerak TKIT Islamic Centre Purwodadi - Anik Sulastri; Nur Fajrie (Peneliti.net, 2023)
One of the things that is the focus of this research is the Cooking Class approach Stealm with primary sources of data in this research, namely the sources of data that are obtained directly from informals on the street. The data comes from students, TKIT Islamic Center, and teachers. Apart from that, secondary sources of data are also used in this research, namely in the form of documents that have already been developed, such as articles that explain about stealth learning methods, as well as important documentation in the learning process that is close to this research. Learning with the STEAlM approach is considered to be incapable of developing students' motor skills, such as an independent student's ability to think critically with learning to be calculative in learning malsallalm to be able to use science and technology in harmony with life's benefits. This is in line with the development which is a factor in the student's motor development.